SYNTHESIS OF EIGHT MIDDLE LOST MECHANISMS FINALLY DISCHARGED DISCREET POSITIONS (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The author has developed the algorithm for the synthesis of eight kinematic structures to generate random function of the positions by given n-number approximate nodes. Synthesis was performed at extreme distances at n≤6. In practice, an approximate synthesis is proposed, with the error being zero only in the approximate nodes, and in the remaining points the error is plotted graphically. According to preset 6 approximate nodes we determine the metric parameters of a family of mechanisms from which we choose the optimal (with the least relative error in the movement of the executive unit). The determination of the position, speed and acceleration function of the executive unit is shown graphically. To establish the authenticity of synthesis is an example.